2009
DOI: 10.1177/039139880903201007
|View full text |Cite
|
Sign up to set email alerts
|

INR Deviations in Hemodialyzed Patients under Low Dose Oral Anticoagulant Therapy

Abstract: The aim of this retrospective study was to evaluate the International Normalized Ratio (INR) in hemodialyzed uremic patients under treatment with oral anticoagulation drugs. Eleven out of one hundred and forty-two uremic hemodialyzed patients in our unit were included in the study. These 11 patients aged from 70 to 85 (mean: 76 years) were under oral anticoagulation treatment for protection from thromboembolic events. They received 1 mg acenocumarol daily with the therapeutic goal of achieving an INR between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…In our study, in spite of a higher frequency of INR measurements compared to other studies (measurements every 21-31 days [28,29]) the percentage of INR in target range did not exceed 54%. The indication for OAT may influence the percentage of INR measurements in target range both as an independent risk factor and via the height and width of target range [7,38,39].…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…In our study, in spite of a higher frequency of INR measurements compared to other studies (measurements every 21-31 days [28,29]) the percentage of INR in target range did not exceed 54%. The indication for OAT may influence the percentage of INR measurements in target range both as an independent risk factor and via the height and width of target range [7,38,39].…”
Section: Discussioncontrasting
confidence: 91%
“…This is the first study analysing the quality of OAT control in patients treated with phenprocoumon in a chronic haemodialysis population. [29]. Both individual and population based percentage of measurements in target range can be biased by more frequent measurements in patients with difficult adjustment of OAT, resulting in an underestimation of OAT control [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of blood proteins, especially albumin, to bind warfarin is very strong, and therefore changes in their concentration during HD result in significant changes in the concentrations of the active ingredient of the medicine, INR, and, consequently, treatment complications. In a retrospective study of 142 haemodialysed patients who received acenocoumarol for typical indications at a dose of 1 mg a day for a year, Gompou et al [27] demonstrated that 30% of the INR values determined at this time were below target values, 37% were in the therapeutic range, and nearly 33% exceeded therapeutic values. Admittedly, there is no information regarding the severe complications of such treatment in the report, but the fact that OACs were overdosed in 1/3 of the cases seems alarming.…”
Section: Chronic Kidney Disease and Oral Anticoagulant Treatmentmentioning
confidence: 99%